Strategic participatory forest management system for sustainable forestry development - Luján-Álvarez, Concepción; Olivas-García, Jesús Miguel; Vázquez Álvarez, Susana; Hernández-Salas, Javier; Castruita-Esparza, Luis Ubaldo (Instituto de Ecología, A.C., 2021)
The impacts of economic globalization are manifested on the social, economic-financial, institutional and environmental, dimensions, in a society economically governedfrom the top-down. In Mexico, these effects have created the need to develop the forestry sector with sustainability vision. The objective is to present a participatory strategic forest management system that promotes sustainable forestry development. The strategic management system is integral, systematic, adaptive, and is philosophically based on strategic thinking, holistic vision, and participatory democracy. It includes "bottom-up" decision-making in compliance with the established regulations. The system is established with the design, application, multidimensional support, and monitoring for sustainable forestry development in the ejido el Largo y Anexos, Chihuahua, Mex. Five axes of development were defined: forest management and biodiversity, forest supply and production, industrial development, market development, and organization and management. As a result, progress has been made in the different axes of development established: improvement of organizational and management levels, better productivity, good forest management, increased employment, and market opportunities, among others. In conclusion, the system is characterized by being comprehensively different from the traditional model of forestry development in forest ejidos. It promotes participatory, anticipatory, and self-managed community forestry development, since the forest ejidos are those who live with the effects of the actions taken in their community. It represents a paradigm shift. It can be replicated at the local, regional, and national levels under different social, economic and environmental conditions.